(Toulouse) Marine - Théodule Ribot - Laren, Singer Museum, Pays-Bas - Didier Descouens (Wikimedia Commons, 2021)
Notice iconographique issue de Wikimedia Commons. Titre: (Toulouse) Marine - Théodule Ribot - Laren, Singer Museum, Pays-Bas.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures